183 Significance of body mass index change during concomitant chemo radiation in locally advanced cervical cancer. (18th September 2019) - Kaabia, O; Nourallah, G; Aymen, L; Rym, Z; Mohamed, B; Hédi, K; Slim, BA; Noureddine, B
Abstract : Objectives: To evaluate the influence of body mass index (BMI) changes during concomitant chemotherapy and radiotherapy on oncologic and surgical outcomes in women with locally advanced cervical cancer. Methods: This is a monocentric prospective study including 106 patients with locally advanced cervical carcinoma (FIGO Stage IB2 and more) that were allocated concomitant chemotherapy and radiotherapy (CCR) with an inclusion period from 2000 to 2009 and a follow up until 2018. We calculated the BMI of the patients on the first day of each therapy session and on the day of the final MRI and on the day of the surgery. Results: The mean BMI at baseline and the final MRI was 35.1±5.6 and 33.9±4.5 kg/m 2 (P=0.046), respectively. During the CCR, 51 (48.1%), 29 (27.4%), and 26 patients (24.5%) had weight loss, no weight change, and weight gain, respectively, of which 11 (10.4%) had 10% or more weight loss and 20 (18.9%) had 10% or more weight gain. A pre-treatment BMI of ≥25kg/m2 was significantly associated with a higher complete response rate to the CCR (P=0.03) and a lower 10 year recurrence rate (P=0.043). A post-treatment BMI of ≥25kg/m 2 was a significant factor for low recurrence rate (P=0.049). However, weight change during CCR was not significantly associated with complete response or 10 years recurrence rate. Pre and post-treatment BMIs changes were not associated with lower surgical complications rates. Conclusions: The BMI variation in patients undergoing CCR for locally advanced cervical cancer may alter the response and the prognosis, with no impact on surgical complications